Differences In Caregiver Burden Of Child Patients With Attention Deficit Hyperactivity Disorder And With Autism Spectrum Disorder At the West Java Provincial Mental Hospital and Grha Atma Main Clinic - Arlisa Wulandari; Rr. Desire Meria Nataliningrum; Chalda Surya Ramadhan (Sean Institute, 2025)
Caregivers are individuals who provide assistance to those unable to carry out daily activities due to illness. They play a crucial role in offering support and aid to patients. Caregiver burden represents the pressure experienced by caregivers while attending to patients, encompassing physical, psychological, social, and financial strains. This research aims to explore whether there are differences in caregiver burden between caregivers of children with Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) at the Mental Health Hospital in West Java Province and Grha Atma Primary Clinic. Additionally, the study seeks to determine which caregiver burden is more substantial. This was a cross-sectional analytical study utilized purposive sampling, with 70 respondents, including 35 caregivers of ADHD patients and 35 caregivers of ASD patients. Primary data collection involved sociodemographic questionnaires to assess caregiver characteristics and the Zarith Burden Interview (ZBI) in Indonesian, consisting of 22 questions to measure caregiver burden. Univariate and bivariate analyzes were employed, and the results, presented in narrative and tabular form, revealed a significant difference in caregiver burden between ADHD and ASD caregivers. Overall, the caregiver burden for ASD (42.34) was found to be higher compared to ADHD caregivers (28.66). Based on these findings, the study recommends healthcare professionals at the Mental Health Hospital in West Java Province and Grha Atma Primary Clinic to provide counseling on workload management to prevent caregivers from experiencing excessive burdens.